2013
DOI: 10.1093/jjco/hyt098
|View full text |Cite
|
Sign up to set email alerts
|

A Non-invasive Modality: The US Virtual Touch Tissue Quantification (VTTQ) for Evaluation of Breast Cancer

Abstract: Objective: We evaluated the biologic features of breast tissues using a newly developed noninvasive diagnostic system, named virtual touch tissue quantification. Methods: A total of 180 patients including 115 invasive ductal carcinoma, 30 ductal carcinoma in situ, 4 mucinous carcinoma, 7 invasive lobular carcinoma, 8 fibroadenoma, 12 fibrocystic change and 4 intraductal papilloma were studied at Nahanishi Clinic, Okinawa. We first compared the results of virtual touch tissue quantification according to each hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Being the quantitative measurement of shear wave elastography based on acoustic radiation force impulse (ARFI), Virtual Touch Tissue Quantification (VTTQ) (Nightingale et al 2002;Fahey et al 2007;McAleavey et al 2007;Tamaki et al 2013) is a quantitative measurement of shear wave velocity generated by ARFI, allowing both the qualitative visual and quantitative evaluation of the elasticity of the tissue concerned. This method could evaluate the stiffness of tissues such as muscles, tendons, abdominal organ, breast and prostate, providing complementary mechanical characteristics of the tissue concerned, in addition to conventional physical and morphological information provided by sonogram.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being the quantitative measurement of shear wave elastography based on acoustic radiation force impulse (ARFI), Virtual Touch Tissue Quantification (VTTQ) (Nightingale et al 2002;Fahey et al 2007;McAleavey et al 2007;Tamaki et al 2013) is a quantitative measurement of shear wave velocity generated by ARFI, allowing both the qualitative visual and quantitative evaluation of the elasticity of the tissue concerned. This method could evaluate the stiffness of tissues such as muscles, tendons, abdominal organ, breast and prostate, providing complementary mechanical characteristics of the tissue concerned, in addition to conventional physical and morphological information provided by sonogram.…”
Section: Introductionmentioning
confidence: 99%
“…This potentially improves the characterization of tissues and focal lesions in an objective way. VTTQ thus represents a good tool for the quantification of the intrinsic property of the tissue, and could provide objective and reproducible data (Nightingale et al 2002;Fahey et al 2007;McAleavey et al 2007;Tamaki et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, shear wave imaging including point shear wave speed (SWS) measurement and SWS imaging has been introduced into clinical practice. Point SWS measurement such as virtual touch tissue quantification (VTQ; Siemens Medical Solutions, Mountain View, CA, USA) can measure the SWS of tissue and several studies showed that point SWS measurement is useful in differentiation between benign and malignant breast lesions101112. Nonetheless, point SWS measurement is not able to provide two-dimensional (2D) stiffness distribution of target lesion.…”
mentioning
confidence: 99%
“…Virtual Touch tissue quantification enables a simultaneous quantitative evaluation of tissue stiffness by measuring the SWV. Acoustic radiation force impulse imaging does not require any external stress, even in deep tissues, and is less operator dependent compared with strain elastography . Nevertheless, LNs with superficial locations and soft compositions may decrease the effectiveness of SWVs …”
Section: Discussionmentioning
confidence: 99%